Strategies for therapeutic optimization and proactive care in chronic obstructive pulmonary disease (COPD): an Italian expert opinion - Paola Rogliani; Massimo Andreoni; Francesco Dentali; Claudio Micheletto; Andrea Montagnani; Nicola Montano; Alberto Papi; Alessandro Rossi; Pierachille Santus (Internal and Emergency Medicine, 2026)
Abstract Chronic obstructive pulmonary disease (COPD) remains a major public health challenge, characterized by substantial underdiagnosis, high morbidity and mortality, and significant healthcare burden. In Italy, the gap between estimated and diagnosed prevalence highlights the need for improved early detection and proactive management. This expert opinion, developed by a multidisciplinary panel, translates current evidence into practical recommendations tailored to the Italian healthcare context. Patient characterization has moved from a spirometry-centered approach to a proactive, multidimensional model integrating symptom burden, exacerbation history, and cardiopulmonary risk. Early diagnosis should be driven by structured case-finding in primary care and internal medicine, using spirometry for confirmation. Early identification of uncontrolled patients relies on standardized tools, including symptom quantification (CAAT score) and indirect markers like recurrent antibiotic or oral corticosteroid use. Exacerbations are critical events that accelerate both pulmonary and cardiovascular deterioration, identifying a high-risk phase requiring prompt reassessment and optimization. In this context, single-inhaler triple therapy (SITT) is the only pharmacological strategy consistently associated with reduced exacerbations and all-cause mortality in high-risk populations. Timely SITT use may also reduce cardiopulmonary risk. Furthermore, preventing exacerbations limits antibiotic and systemic corticosteroid use, promoting antimicrobial stewardship and mitigating resistance. This expert opinion emphasizes the need for integrated care pathways, standardized clinical tools, and multidisciplinary coordination to overcome therapeutic inertia. A shift toward early identification, timely intervention, and prevention-oriented strategies is essential to improve outcomes and reduce the systemic burden of COPD.